RESTORATIVE JUSTICE FORMULATION POLICY IN THE CHILD CRIMINAL JUSTICE SYSTEM IN INDONESIA - M. Luqman Hakim Siregar; Kasim; Robert Napitupulu; Roland Banjarnahor; Syaiful Asmi Hasibuan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The discussion in this journal focuses on Restorative Justice Formulation Policy in the Juvenile Criminal Justice System. The aim of this research is to be able to properly analyze the basic ideas contained in restorative justice, its relation to children who are in conflict with the law and to be able to analyze the policy formulation regulated in Law no. 11 of 2012 concerning the Juvenile Criminal Justice System to realize restorative justice for children in conflict with the law. Meanwhile, the type of research used in this scientific journal is normative legal research, because it is based on the assessment that there is a conflict of norms between Law no. 11 of 2012 concerning the Juvenile Criminal Justice System with norms contained in the Criminal Code (KUHP). In this case, for unlawful acts committed by children who are not yet 18 (eighteen years old), diversion efforts are carried out with the aim of creating a balanced focus of attention between the interests of the perpetrator and the victim and also paying attention to the impact of resolving criminal cases that occur in society to ensure and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity, as well as receive protection from violence and discrimination.